2019
DOI: 10.1292/jvms.18-0531
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphic adenoma of the mandibular salivary gland in a captive African pygmy hedgehog (<i>Atelerix albiventris</i>)

Abstract: A 3.9-year-old female African pygmy hedgehog ( Atelerix albiventris ) had a firm, tan-colored mass with an uneven surface arising from the mandibular salivary gland. A histopathologic examination revealed that the mass was composed of neoplastic proliferation of epithelial and spindle cells. The neoplastic spindle cells showed positive for vimentin, smooth muscle actin, calponin and cytokeratin 14 and, negative for cytokeratin 19, suggesting that spindle cells were derived from myoepithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Nevertheless, little is known about this species compared to traditional pet animals. Therefore, this is currently a widely studied animal (Chambers et al., 2018; Díaz‐Delgado et al., 2018; Go et al., 2019; Iacob & Iftinca, 2018; Koizumi & Kondo, 2019; Muñoz‐Gutiérrez et al., 2018; Needle et al., 2019; Okada et al., 2018; Spugnini et al., 2018). Although the lingual morphology is well known in the majority of pet animals, this information is still lacking in some species which have become popular pets in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, little is known about this species compared to traditional pet animals. Therefore, this is currently a widely studied animal (Chambers et al., 2018; Díaz‐Delgado et al., 2018; Go et al., 2019; Iacob & Iftinca, 2018; Koizumi & Kondo, 2019; Muñoz‐Gutiérrez et al., 2018; Needle et al., 2019; Okada et al., 2018; Spugnini et al., 2018). Although the lingual morphology is well known in the majority of pet animals, this information is still lacking in some species which have become popular pets in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Salivary gland neoplasms are uncommon in all veterinary species, occurring most often in dogs and cats, 11,13 rarely in cattle, 2,16,17 and sporadically in nontraditional species [5][6][7] ; they remain unreported in swine. 13 A retrospective study including almost 600 tumors in cattle over a 45-y period identified no salivary neoplasms.…”
mentioning
confidence: 99%
“…IHC has been utilized in the differentiation of MECs. Epithelial cells display diffuse positivity for cytokeratin not only in MECs but in adenocarcinomas, 6 pleomorphic adenomas, 7 basal cell adenocarcinomas, 5 and squamous cell carcinomas. 13 Peripheral cells in MECs can stain positive for vimentin, 6 and 20–25% of epithelial cells in MECs co-express vimentin and glial fibrillary acidic protein.…”
mentioning
confidence: 99%